All Days 1998
DOI: 10.4043/8586-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Completion Techniques Applied to a Deepwater Gulf of Mexico TLP Completion Successfully Gravel Pack an Openhole Horizontal Interval of 2400 Feet

Abstract: As the scope of development continues to expand, more instances are being noted in which traditional technologies cannot satisfy job parameters. In deepwater projects, for example, high-rate production and completion reliability present major challenges to operators, and traditional methods of sand control often have not been able to address the changing conditions. In this paper, a solution that combines gravel packing, enhanced downhole tool capability, and advanced fluid technology is used in an offshore en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Several researchers reported that to obtain a successful gravel pack for highly deviated and horizontal wells the fluid flow in screenwash pipe annulus also must be minimized. [12][13][14][15] During the Alpha-Beta wave building up and propagation process, the gravel will be deposited and the fluid will flow along the least resistance path. Figure 1 is a schematic of the Alpha wave building up process.…”
Section: Dynamic Alpha Wave Height Calculationmentioning
confidence: 99%
“…Several researchers reported that to obtain a successful gravel pack for highly deviated and horizontal wells the fluid flow in screenwash pipe annulus also must be minimized. [12][13][14][15] During the Alpha-Beta wave building up and propagation process, the gravel will be deposited and the fluid will flow along the least resistance path. Figure 1 is a schematic of the Alpha wave building up process.…”
Section: Dynamic Alpha Wave Height Calculationmentioning
confidence: 99%
“…A packer test assembly 6 and an actuated reverse ball seat 7 were selected to address occurrence of this problem. During packer setting, packer testing, and reverse circulation, fluid can be continuously fed to the formation to keep pressure on the filter cake.…”
Section: Planned Proceduresmentioning
confidence: 99%
“…The mainbore lateral completion will use conventional openhole gravel-pack equipment, 8,9 as before. Once the mainbore gravel pack is completed, a bridge plug will be used to provide isolation to the mainbore completion.…”
Section: Conceptual Applicationsmentioning
confidence: 99%